Smectic A mesophases from luminescent sandic platinum(II) mesogens. Issue 12 (25th September 2016) - Krikorian, Markrete; Voll, Constantin-Christian A.; Yoon, Maryam; Venkatesan, Koushik; Kouwer, Paul H. J.; Swager, Timothy M.
ABSTRACT: Square planar platinum(II) thienyl pyridyl complexes with board-shaped structures assemble into lamellar (SmA) liquid crystal phases at elevated temperatures. Liquid crystals of this type are expected to have stronger biaxial correlations than typical calamitic mesogens. The mesophase stability improves with decreasing alkyl chain lengths with C8 H17 having the widest range of stability. All complexes are luminescent in solution. GRAPHICAL ABSTRACT: